2005
DOI: 10.1128/aem.71.8.4372-4379.2005
|View full text |Cite
|
Sign up to set email alerts
|

Two Rhizobial Strains,Mesorhizobium lotiMAFF303099 andBradyrhizobium japonicumUSDA110, Encode Haloalkane Dehalogenases with Novel Structures and Substrate Specificities

Abstract: Haloalkane dehalogenases are key enzymes for the degradation of halogenated aliphatic pollutants. Two rhizobial strains, Mesorhizobium loti MAFF303099 and Bradyrhizobium japonicum USDA110, have open reading frames (ORFs), mlr5434 and blr1087, respectively, that encode putative haloalkane dehalogenase homologues. The crude extracts of Escherichia coli strains expressing mlr5434 and blr1087 showed the ability to dehalogenate 18 halogenated compounds, indicating that these ORFs indeed encode haloalkane dehalogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…The enzyme activities of the haloalkane dehalogenases toward various substrates have been assessed, and it was reported that DbjA showed higher dehalogenation activity for substrates carrying a bulky substituent at the β position than did LinB (Sato et al, 2005). Such information on substrate specifi city will provide clues on ways to alter the substrate specifi city of this unique class of enzymes.…”
Section: Cloning and Dna Sequencing Of Group II Dehalogenase-encodingmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme activities of the haloalkane dehalogenases toward various substrates have been assessed, and it was reported that DbjA showed higher dehalogenation activity for substrates carrying a bulky substituent at the β position than did LinB (Sato et al, 2005). Such information on substrate specifi city will provide clues on ways to alter the substrate specifi city of this unique class of enzymes.…”
Section: Cloning and Dna Sequencing Of Group II Dehalogenase-encodingmentioning
confidence: 99%
“…Although there is only limited information on the diversity of bacterial haloacetic acid dehalogenases, the homologous proteins (or the corresponding genes) of haloalkane dehalogenases LinB from Sphingobium japonicum strain UT26 (Nagata et al, 1993) have been found in various bacteria, including Mesorhizobium loti strain MAFF303099 (DmlA), Bradyrhizobium japonicum USDA110 (DbjA) (Sato et al, 2005), and Mycobacterium avium strain N85 (DhmA) (Jesenska et al, 2005). The enzyme activities of the haloalkane dehalogenases toward various substrates have been assessed, and it was reported that DbjA showed higher dehalogenation activity for substrates carrying a bulky substituent at the β position than did LinB (Sato et al, 2005).…”
Section: Cloning and Dna Sequencing Of Group II Dehalogenase-encodingmentioning
confidence: 99%
“…2A). Several haloalkane dehalogenases studied to date have been shown to have broad substrate ranges (6,15), and to dehalogenate chlorinated ethers (6,26) and alcohols (9). The dehalogenation of a chlorinated alcohol ether by these enzymes, however, may be a novel reaction.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Several haloalkane dehalogenases studied to date have been shown to have broad substrate ranges (7,16) and to dehalogenate chlorinated ethers (7,27) and alcohols (11). The dehalogenation of chlorinated alcohol ethers by these enzymes, however, may be a novel reaction.…”
Section: Resultsmentioning
confidence: 99%